A study of users' acceptance and satisfaction of emergency call service. (7th July 2016) - Chariete, Abderrahim; Bakhouya, Mohamed; Nait‐Sidi‐Moh, Ahmed; Ait‐Cheik‐Bihi, Wafaa; Gaber, Jaafar; Kouta, Raed; Wack, Maxime; Lorenz, Pascal
Summary: In recent years, there has been rapid and significant development of road transport technologies in order to reduce the number of killed and injured people on roads. These include safety technologies, emergency call systems (eCall), and advanced traveler information systems. The eCall system is an automatic in‐vehicle emergency call service, which is mainly used for notifying emergency services about dangerous road situations and their exact location. In this paper, an eCall platform prototype is developed to allow quick and efficient rescue of injured people in dangerous road situations. The eCall function is developed and installed in nomadic devices (e.g., smartphones and tablets). Large‐scale field operational tests were conducted in real settings to assess the impacts of the eCall function provided by in‐vehicle nomadic devices. More precisely, experiments were conducted by more than 250 participants with different sociodemographic profiles in order to study the users' acceptance of the use of the developed eCall function for large‐scale usage. The collected data are analyzed, and results are reported. Performed experiments showed the usefulness, acceptance, and satisfactory performance of the eCall service. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The eCall system automatically initiates a voice call to the emergency service when a serious accident occurs. It communicates much information (user id, GPS coordinates, etc.), even if the driver is not able to make a phone call. This will help emergency services to provide quick assistance to driver and passengers. This could save up to 2500 lives per year.